FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PNEUMONIA PADA BALITA - Sari, Riani Dwi Indah (JURNAL MEDIA KESEHATAN, 2016)
Pneumonia is one of the causes of infant mortality. The percentage of pneumonia inIndonesia in 2009 increased (49.23%) and in 2010, falling to (39.38%) of the number ofinfants in Indonesia. In as many as 16.401 cases of Bengkulu province. The high incidence ofpneumonia were found in 214 cases Curup health center. The purpose of this study determinethe relationship of the factors associated with the incidence of pneumonia in infants CurupWork Area Health Center in 2013. This study used a case-control method with a number of38 samples were taken in total control sampling and 38 samples were taken by simple randomsampling. The place and time of the study, in Curup Health Center in January 2014. Retrievalof data using a data collection sheet was analyzed using Chi-square. Univariate analysisshowed almost all of the infants (89.5%) did not LBW, most of the infants (65.8%) hadcomplete immunization status and most of the infants (68.4%) were exclusively breastfed. Inbivariate analysis showed that risk factors have a relationship with the pneumonia is exclusivebreastfeeding (OR = 3.714), immunization status (OR = 3.375) and the risk factors associatedwith pneumonia is not LBW(OR = 0.521).